Pursuing Urban Liveability with Nature-Based Solutions. A Multi-Faceted Strategy Towards Sustainability - De Nardis, Silvia (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
In an age of high anthropic pressure on the environment, cities seek to innovate their strategies in favour of greater urban liveability. This means searching for effective solutions to ensure citizens’ well-being, health, productivity and social inclusion. Among the various ongoing trials, nature-based solutions seem to promisingly contribute to realising liveable urban contexts. Created to deal with the costs of climate change, ecosystem degradation and biodiversity loss, they soon became a multi-faceted strategy via which to tackle societal challenges. This paper explores the role of nature-based solutions in addressing collective needs at an urban scale, investigating their relationships with social innovation processes and focussing attention on urban-greening solutions. It investigates the transformative potential of nature-based solutions in producing sustainable liveability and focusses on the implementation-process elements with the potential to affect policies, governance and practices. The analysis of the opportunities for a dynamic and liveable environment to create new and positive scenarios for profound mainstreaming change is included. The study deepens the case of UIA UPPER Latina, a project devoted to the urban regeneration of abandoned and degraded areas by using co-designed and self-produced nature-based solutions. It represents a pioneering experience in the European production and management of parks, being characterised by the ambition to integrate greenness with innovative services in the educational, social and economic sectors. A continuous process of collaboration between various stakeholders–in the public-private-people partnership model–gives rise to a dynamic and open community of practice that is still in progress. The results suggest that nature-based solutions can represent tools that if incorporated into an integrated and multi-level strategy, will help meet urgent needs, foster vibrant and liveable systems, activate innovative processes and stimulate awareness of sustainable transitions.